2021
DOI: 10.1186/s12886-021-01978-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, severity, and risk factors for dry eye disease in Dubai – a cross sectional study

Abstract: Background The prevalence of dry eye disease is increasing globally and requires the attention of healthcare professionals as it worsens patients’ quality of life. No published studies on the epidemiology of dry eyes have been found in Dubai. Purpose To describe the epidemiology, prevalence, severity, and associated factors of dry eyes in Dubai, United Arab Emirates, in 2019. Methods This was an analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
3
26
2
1
Order By: Relevance
“…So far, advancing age, female gender, and smoking are the most common factors associated with DED ( 21 ), which were consistent with our findings. However, another population-based investigation in Dubai showed that daily screen time (> 6 h) was positively associated with dry eyes ( 22 , 23 ), while no association between daily screen exposure time and DED was found in this study. This discrepancy might be due to the different lifestyle of the study participants.…”
Section: Discussioncontrasting
confidence: 89%
“…So far, advancing age, female gender, and smoking are the most common factors associated with DED ( 21 ), which were consistent with our findings. However, another population-based investigation in Dubai showed that daily screen time (> 6 h) was positively associated with dry eyes ( 22 , 23 ), while no association between daily screen exposure time and DED was found in this study. This discrepancy might be due to the different lifestyle of the study participants.…”
Section: Discussioncontrasting
confidence: 89%
“…As shown in Figure 1 , the prevalence of DED in our participants was 55.9%, the majority of which had mild DED (23.6%). The prevalence is similar to that in a study conducted in Dubai (62.6%) 17 and in the Eastern region of Saudi Arabia (62.4%). 3 However, in a study conducted in Al-Ahsa, the prevalence was lower (32.1%).…”
Section: Discussionsupporting
confidence: 88%
“…3 Conversely, some studies found no significant association between sex and OSDI score. 21 , 22 Although several studies have shown a significant association between age group and DED, 4 , 17 our results revealed no such association.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations